İşbirliği ile öğretim yöntemine dayalı beden eğitimi derslerinin 9–10 yaş grubu çocukların temel motor becerileri ile problem çözme becerilerinin gelişimine etkisinin araştırılması - Altınkök, Mustafa (My University, 2012)
Bu araştırma, 12 haftalık İşbirliği ile Öğretim Yöntemine Dayalı Beden Eğitimi programının, 9–10 yaş grubu çocukların temel motor becerileri ile problem çözme becerileri gelişimine etkisini incelenmek amacıyla yapılmıştır. Bu amaç doğrultusunda öğretim programında işbirlikli öğrenme tekniklerinden De Vries (1976) ve Slavin (1978–1980) tarafından geliştirilen “Takım–Oyun–Turnuva” ve Johnson ve Johnson (1994) tarafından geliştirilen “Birlikte Öğrenme” yapıları üzerine kurulmuş “Öğrenme Takımları”, Aranson ve arkadaşları (1978), Slavin (1980) ve Kagan (1986) tarafından geliştirilen “Ayrılıp Birleşme” yapısı üzerine kurulmuş “Parça Birleştirme”, Kagan (1992) tarafından geliştirilen “Eş Kontrolü” ve “Düşün–Eşleş–Paylaş” yapısı üzerine kurulmuş “Eşleş–Kontrol et–Uygula” ve “Düşün–Paylaş–Uygula” teknikleri kullanılmıştır. Araştırma, 9–10 yaş grubu çocuklardan oluşmuştur. 69 öğrenci deney (34 erkek 35 kız) ve 70 öğrenci kontrol (35 kız 35 erkek) grubu olarak, 139 öğrenci gönüllü alınmıştır. Araştırmada uygulanan İşbirliği ile Öğretim Yöntemine Dayalı Beden Eğitimi programının çocukların temel motor ve problem çözme becerileri üzerindeki etkisini araştırmak için; el ile top kontrol, ayak ile top kontrol, koşu koordinasyon, statik denge (flamingo), dikey sıçrama, esneklik, durarak uzun atlama, sürat, çeviklik, çabukluk ve tenis topu fırlatma testleri ile Serin ve arkadaşlarının 2010’da geliştirdikleri, “İlköğretim Düzeyindeki Çocuklar İçin Problem Çözme Envanteri” (ÇPÇE) uygulanmıştır. Verilerin çözümlenmesinde istatistik kullanılmıştır. Deney ve kontrol grubu arasındaki farklılığı bulmak için bağımsız t testi, deney ve kontrol grubunun ön–son test arasındaki farklılığı bulmak için ise eşleştirilmiş t testi uygulanmıştır. Anlamlılık düzeyi uygulanan test bataryalarına göre, (p<0,05) ve (p<0,001) olarak değişiklik göstermiştir. İstatistik sonuçlarına göre, deney ve kontrol grubu temel motor beceri ön test değerleri ortalamaları arasında, anlamlı bir farklılık bulunmazken, son test değerleri ortalamaları arasında, deney grubu lehine farkın anlamlı olduğu bulunmuştur (p<0,001). Kontrol grubu ön–son test değerleri ortalamaları arasında; el ile top kontrol, dikey sıçrama ve koşu koordinasyon testlerinde (p<0,001), durarak uzun atlama, tenis topu fırlatma ve esneklik testlerinde (p<0,05) düzeyinde farkın anlamlı olduğu bulunmuş, ayak ile top kontrol, statik denge, 30 m sürat koşusu, çeviklik ve çabukluk testlerinde ise herhangi bir anlamlılık bulunmamıştır. Deney grubunun ön–son test değerleri ortalamaları arasında ise; son testler lehine farkın anlamlı olduğu bulunmuştur (p<0,001). Deney ve kontrol grubu problem çözme becerisi ön test değerleri ortalamaları arasında, anlamlı bir farklılık bulunmazken, son test değerleri ortalamaları arasında Problem Çözme Becerisine Güven ve Kaçınma alt boyutlarında (p<0,001),

denetim alt boyutunda ise, (p<0,05) düzeyinde farkın anlamlı olduğu bulunmuştur. Deney grubu ön–son test değerleri ortalamaları arasında, farkın son testler lehine anlamlı olduğu bulunurken (p<0,001), kontrol grubu ön–son test değerleri ortalamasında Öz denetim alt boyutunda farkın anlamlı olduğu bulunurken (p<0,001), diğer alt boyutlarda herhangi bir anlamlılık bulunmamaktadır. Sonuç olarak, plânlı ve uzun süreli uygulanan İşbirliği ile Öğretim Yöntemine Dayalı Beden Eğitimi ocukların temel motor becerilerini ve problem çözme becerini anlamlı düzeyde geliştirebileceği anlaşılmaktadır. Beden eğitimi, İşbirliği ile öğrenme, Problem çözme becerisi, Temel motor beceriler ABSTRACT This research has been done to examine the efficiency of Teaching Method Based on Physical Education with the collaboration of 12 weeks, on 9–10 years old children's developments of basic motor skills and problem solving skills. The techniques that have been used for this research are; “Team Game Tournament” which is one of the cooperative learning techniques and developed by De Vries (1976) and Slavin (1978–1980); “Learning Teams” which is based on learning together structure and developed by Johnson and Johnson (1994); “Assembling Pieces” which based on the structure seperating and combining and developed by Aranson and friends (1978), Slavin (1980) and Kagan (1986); and Pair off–Control–Apply and Think–Share–Apply techniques which is based on Pairs Control and Think–Pair off–Share and developped by Kagan (1992). The research group composed of children ages between 9-10, there were 69 student as experiments (35 female, 34 males) and 70 control students (35 girls 35 boys) participated on a voluntary basis as a group of 139 students in total. Cooperation with the Faculty of Physical Education program is based on the method applied in the study of children to investigate its effect on the basic motor skills, hand and ball control, foot and ball control, running coordination, static balance (flamingo), vertical jump, flexibility, standing long jump, speed, agility with the tennis ball throwing and agility tests. Cooperation with the Faculty of Physical Education program is based on the method applied in the study, to investigate its effect on children's problem-solving skills; cool and colleagues developed in 2010, “Primary–Level Problem Solving Inventory for Children” (ÇPÇE) were applied. SPSS statistical software was used to analyze the data. To find the difference between the experimental and control group, independent test, both control and experimental group, to find the difference between pre and post-tests, paired samples t test was used. According to test batteries applied to the level of significance (p<0.05) and (p<0.001) has varied. According to statistics, between the experimental and control group pre-test values in hand with the ball control, foot and ball control, running coordination, static balance (flamingo), vertical jump, flexibility, standing long jump, 30 meter sprint, agility and quickness with the no significant difference between the mean values of the tennis ball throwing test was found (p>0.05). Between the pre-test values, with the top hand control, foot and ball control, running coordination, static balance (flamingo), vertical jump, flexibility, standing long jump, 30 meter sprint, agility and quickness with a tennis ball throwing test significant differences between the mean values of the last tests were in favor of the 0.001 level (p<0.001). Between pre-and post-test values of the control group, with the top hand control, vertical jump and running the front–end test values according to the level of coordination motor skills in favor of final tests at the level of 0.001 (p<0.001), standing long jump, tennis ball throwing motor skills and flexibility According to the level of pre–test–post–test values are significantly different at the level of 0.05 in favor of the last tests (p<0.05). Foot and ball control, static equilibrium, 30 m sprint, agility and quickness by level of motor skills pre–test–post–test values have any significance (p>0.05). Between the experimental and the control group's post–test values, with the top hand control, foot and ball control, running coordination, static balance (flamingo), vertical jump, flexibility, standing long jump, 30 meter sprint, agility and quickness with a tennis ball throwing test values there were significant differences between the mean level of 0.001 in favor of the experimental group (p<0.001). Dimensions of problem–solving skills that make up the bottom of the experimental and control groups, problem–solving confidence, self–control and avoidance of problem solving according to the level of significance there is no pre-test values (p>0.05). Forming sub–dimensions of the experimental group problem–solving skills, problem–solving confidence, self–control and avoidance of problem solving skill levels, according to recent tests in favor of pre and post–test values are significantly different at the level of 0.001 (p<0.001). Forming sub-dimensions of the control group problem-solving skills, problem-solving skills according to their level of trust and avoidance of problem solving pre–test values have any significance (p>0.05). Self–regulation according to the level of problem solving in favor of the final tests of the pre–test values are significantly different at the level of 0.001 (p<0.001). Dimensions of problem-solving skills that make up the bottom of the experimental and control groups, problem-solving skills according to their level of trust and avoidance of problem solving in favor of the experimental group post-test values are significantly different at the level of 0.001 (p<0.001). According to the skill level of self–control problem solving in favor of the experimental group post-test values are significant differences in the level of 0.05 (p<0.05). As a result, planned and implemented in collaboration with long-term Method Based on Teaching Physical Education program, children develop basic motor skills and problem-solving skill is understood that significant. Key Words: Physical education, cooperative learning, problem solving skills, basic motor skills
Keywords: Beden Eğitimi ve Spor; Hareket Eğitimi; İşbirliği ile Öğrenme; Motor Becerisi; Problem Çözme Becerisi; Spor, Çocuklarda